Quantitative ultra‐high‐performance liquid chromatography–tandem mass spectrometry for determination of dexmedetomidine in pediatric plasma samples: Correlation with genetic polymorphisms. (10th October 2019) - Guan, Yanping; Li, Bilian; Wei, Wei; Wang, Siyi; Yuen, Vivian‐min; Liu, Yao; Ao, Zheng; Zhou, Shan; Tian, Hang; Huang, Min; Song, Xingrong; Zhong, Guoping
Abstract: Dexmedetomidine is an important sedative agent administered as premedication to achieve procedural sedation in children. To describe the correlation between the genetic state and the concentration of dexmedetomidine, it is necessary to develop a specific, time‐saving and economical method for detection of dexmedetomidine in plasma samples. In this work, an ultra‐high‐performance liquid chromatography (UHPLC)–tandem mass spectrometry method has been established and validated for detection of dexmedetomidine in plasma from pediatric population. After a simple liquid–liquid extraction with an organic solution, the analytes were separated on an ACQUITY BEH C18 column (2.1 mm × 50 mm, 1.7 μm particle size) by gradient elution with the mobile phase of acetonitrile and 1‰ aqueous formic acid (flow rate 0.3 mL min −1 ). Mass spectrometry measurements were performed under the positive selected reaction monitoring and the mass transitions monitored were m/z 201.3 → 95.1, 204.2 → 98.0 for dexmedetomidine and deuterated medetomidine (internal standard), respectively. Validation of the method based on China Food and Drug Administration guidelines showed acceptable selectivity. The UHPLC method employed a stable isotope‐labeled internal standard, showed good specificity and was successfully used to detect dexmedetomidine in plasma samples from 260 pediatric patients. A subsequent application of this method to a pharmacogenetic study was also described. Importantly, this is the first study to report the correlation between CYP2A6 rs835309 activity and concentration of dexmedetomidine.